Openness and efficiency in Brazilian banking - Afonso S. Bevilaqua; Eduardo Loyo (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1998)
Brazil has recently made great strides in opening its domestic banking market to foreign participation, contrary to what one would have expected from its negotiating stance in regional and multilateral fora dealing with trade in financial services. We review the possible gains from such unilateral liberalization move, and proceed to measure one specific gain that appears most promising: improvements in cost efficiency in the production of banking services. Our results indicate that these gains indeed materialized, although not to the same extent in all segments of the banking market.
Keywords: 330